Selection of airfoils for straight-bladed vertical axis wind turbines based on desirable aerodynamic characteristics - Islam, Mazharul; Amin, M. Ruhul; Ting, David S-K; Fartaj, Amir (2008)
Selection of the airfoil is crucial for better aerodynamic performance and dimensions of a smaller-capacity SB-VAWT which can compete with conventional energy sources in niche markets like urban areas and off-grid remote applications for diversified applications. Airfoil related design changes also have the potential for increasing the cost effectiveness of VAWTs. Recently, Islam et. al [1] have identified the desirable features of an ideal airfoil for smaller capacity SB-VAWT to improve its starting characteristics and overall performance. They have shortlisted several aerodynamic characteristics of the desirable airfoil. Based on these desirable aerodynamic characteristics, an attempt has been made in this paper to shortlist ten prospective candidate airfoils for smaller-capacity SB-VAWT. This is done using both experimental and analytical characteristics. Nine performance indices have been defined in this paper in light of desirable aerodynamic characteristics to select best performing airfoil. These performance indices are utilized for considering the following desirable aerodynamic characteristics: (i) stall angle at low Reynolds number, (ii) width of the drag bucket, (iii) zero-lift-drag coefficient, (iv) Cl /Cd ratio, (v) maximum lift-coefficient, (vi) deep-stall angle, (vii) roughness sensitivity, (viii) trailing edge noise generation, and (ix) pitching moment. Here, Cl and Cd are coefficients of lift and drag respectively. After determining the value of the performance indices and rating of the candidate airfoils, the most promising airfoil is selected. Among the ten candidate airfoils, overall rating of NASA LS(1)-0417 has been found to be the best.